Julian of Aeclanum on Pain - Lossl, Josef (Journal of early Christian studies, 2002)
Pain was one of the issues debated between Julian of Aeclanum and Augustine of Hippo. For Augustine pain was an evil caused by original sin. Julian argued that, in the context of creation as a whole, pain can be treated as a good, since its moderate forms are creational. Only in excess are they evil. This article aims at presenting Julian's position in detail, not only in the context of the debate with Augustine, but in the wider context of late ancient philosophy and early Christian doctrine. Julian is well acquainted with philosophical and medical texts and with the biblical and patristic tradition. He rejects Augustine's attempt to work all these into a universal theological theory of pain and thereby deny, in Julian's view, philosophy and medicine their relative autonomy. Julian's plea-as a theologian-for a rational and empirical approach to pain draws as much upon ancient sources as it anticipates an attitude towards natural science and philosophy usually associated with much later periods in history.